Maxillofacial trauma severity effects in patients with head injury in a tertiary care center in Yogyakarta, Indonesia - Putri, Sandy Nur Vania; Fauzi, Aditya Rifqi; Paramita, Dewi Kartikawati; Dachlan, Ishandono; Seswandhana, Rosadi (Springer Science and Business Media Deutschland GmbH, 2022)
Background: Traumatic brain injury (TBI) is one of the leading causes of death and disability worldwide. In various combinations, a high frequency of facial bone fractures has been reported. However, the results are still conflicting. Methods: We retrospectively reviewed medical records of patients with maxillofacial trauma who were admitted to Dr. Sardjito Hospital, Yogyakarta, Indonesia, between January 2016 and December 2017. Results: A total of 70 patients with maxillofacial trauma were involved (57 males and 13 females, 18–65 years). Moreover, most of them were 18–25-year-old males (34.3). The average patient age was 35.5 ± 14 years. No significant association was found between the sex and age group of the patient (p = 0.774). Motorcycle accident was the most frequent cause of maxillofacial fractures (84) with midfacial and multiple maxillofacial fractures being the most frequent types found in patients (40 and 40, respectively). The most common facial fracture was in the zygomatic bone (28) and most cases showed mild facial injury (81). A significant association was found between the Glasgow Coma Scale (GCS) and types of traumatic brain injury (TBI) (p = 0.031). However, when GCS was compared with facial injury, no statistically significant level was reached and its correlation was low (p = 0.267, r = 0.134). Conclusions: There was a significant association between types of traumatic brain injury with head injury severity. However, we found no correlation between head injury severity and facial injury severity. To explain and validate our results, further multicenter studies with a larger sample size are required. Level of evidence: Level IV, Risk/Prognostic. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.